PARC_CL 2.0 crack model for NLFEA of reinforced concrete structures under cyclic loadings. (15th October 2017) - Belletti, Beatrice; Scolari, Matteo; Vecchi, Francesca
Highlights: Implementation of a fixed crack model, named PARC_CL 2.0 (Physical Approach for Reinforced Concrete for Cyclic Loading), characterized by smeared reinforcement. PARC_CL 2.0 allows to take into account plastic deformations and hysteretic cycles. The model presents some improvement, with respect crack model available in commercial code material library. The model permits to predict with good accuracy the experimental data of RC panels subjected to cyclic loadings. Abstract: This paper presents the development of an updated version of PARC_CL 2.0 crack model implemented in Abaqus Code using subroutine UMAT.for. The PARC_CL 2.0 model is a fixed cracked model for the response prediction of reinforced concrete members. More refined material constitutive relationships were incorporated in the formulation of the model to take into account plastic deformations. Finally, to validate the model, reinforced concrete (RC) panels subjected to cyclic loads, available in literature, are modeled and compared with experimental observations. The PARC_CL 2.0 model was able to capture, with reasonable accuracy, the overall behaviour including cyclic shear stress vs. shear strain behaviour, shear stiffness, cyclic stiffness degradation, energy dissipation during the cycles and pinching effect.